FACTORS INFLUENCING HOUSING AFFORDABILITY STRESS VERSUS ALTERNATIVE FINANCING SCHEMES FOR HOME BUYERS IN KLANG VALLEY MALAYSIA - HUA SIONG, Wong; RADHAKRISHNA, Gita (Studia Universitatis Babeș-Bolyai Negotia, 2019)
Objective: The massive uncontrolled development of residential properties especially in the Klang valley has resulted in a supply glut. According to economic theory, when supply exceeds demand, the price product price should decrease. However, due to the increased cost of construction materials and labour, house prices have not decreased. Consequently many in the Klang valley cannot affort to buy residential property causing financial stress to families with a household income below the average level. At the 19th National Housing and Property Summit 2016, Tan Sri Noh Omar the then Minister for Urban Wellbeing, Housing and Local Government Housing, announced an alternative home financing scheme offered through eligible housing developers licensed under the Money Lenders Act 1951 and Pawnbrokers Act 1972. The paper therefore explores factors influencing housing affordability stress and alternative schemes that could be offered by developers without unduly burdening the home buyer and ensuring a balance between the interests of the public and the developer. Methodology: The writers apply the method of documentary studies, historical archives, public record and interview to arrive at the findings. Results: The loan tenure would be between 10 to 20 years with the interest rate being fixed at 12% per annum for borrowers with collateral, and 18% for those without. It is noted that the section of public applying for such a scheme would be those whose monthly income and expenditure disqualify them from a 100% conventional loan. Consequently, one of the immediate issues for the borrower would be coping with the very high interest rates under this scheme. If a borrower were to apply under this scheme as a top-up to a conventional bank loan, there would be two monthly loan repayments to manage. Further if the second loan is without security he would be charged 18% interest leading to a real danger of potential insolvency. Further, no eligibility criteria has been set for developers to qualify for a licence. There is also the issue of a conflict of interest when a developer also acts as a financier. Implication: This research presents a conceptually yet empirically supported framework to describe the factors influencing housing affordability stress and alternative schemes that could be offered by developers by taking into consideration of the legal impact when the developers act as home loan financier to the borrowers. The study is particularly useful for housing industry by identifying the legal implication when the developers act as home loan financier to the borrowers. This paper gives valuable reference to law markers to consider whether this alternative is one of the solutions to solve housing affordability stress in Klang Valley area. JEL classification: H31